2021
DOI: 10.1016/j.msard.2021.103163
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy in adults with multiple sclerosis in the United States: A follow up survey during the initial vaccine rollout in 2021

Abstract: Background: Multiple sclerosis (MS) organizations have recommended that adults with MS obtain the COVID-19 vaccination. Vaccine hesitancy is a barrier to full COVID-19 inoculation in the general population. Whether vaccine hesitancy is also a barrier towards optimizing vaccination rates in the MS community is unknown. To investigate vaccine hesitancy and inform efforts to increase vaccine uptake in the MS population, we conducted a follow up survey of a national sample of adults with MS living in the United St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
55
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 17 publications
4
55
0
1
Order By: Relevance
“…Race/ethnicity . Whites ( Malik et al, 2020 , Dalal et al, 2021 , Thompson et al, 2021 , Ehde et al, 2021 ), Asians ( Szilagyi et al, 2021 , Malik et al, 2020 , Shaw et al, 2021 , Shekhar et al, 2021 , Thompson et al, 2021 , Townsel et al, 2021 ) and American Indians/Alaska Natives ( Malik et al, 2020 , Stern et al, 2021 ) were found to be more likely to vaccinate against COVID-19. However, compared to White race, Black race and Hispanic/Latinx origin were associated with 2 to 6-fold ( Daly and Robinson, 2021 , Fisher et al, 2020 , Latkin et al, 2021 , Salmon et al, 2021 , Nikolovski et al, 2021 , Halbrook et al, 2021 , Saluja et al, 2021 , Caban-Martinez et al, 2021 , Townsel et al, 2021 , Bass et al, 2021 , Jacobi and Vaidyanathan, 2021 , Yang et al, 2021 , Nguyen et al, 2021 ) and 2 to 3-fold ( Fisher et al, 2020 , Latkin et al, 2021 , Saluja et al, 2021 , Caban-Martinez et al, 2021 ) higher chance of being COVID-19 vaccine hesitant, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Race/ethnicity . Whites ( Malik et al, 2020 , Dalal et al, 2021 , Thompson et al, 2021 , Ehde et al, 2021 ), Asians ( Szilagyi et al, 2021 , Malik et al, 2020 , Shaw et al, 2021 , Shekhar et al, 2021 , Thompson et al, 2021 , Townsel et al, 2021 ) and American Indians/Alaska Natives ( Malik et al, 2020 , Stern et al, 2021 ) were found to be more likely to vaccinate against COVID-19. However, compared to White race, Black race and Hispanic/Latinx origin were associated with 2 to 6-fold ( Daly and Robinson, 2021 , Fisher et al, 2020 , Latkin et al, 2021 , Salmon et al, 2021 , Nikolovski et al, 2021 , Halbrook et al, 2021 , Saluja et al, 2021 , Caban-Martinez et al, 2021 , Townsel et al, 2021 , Bass et al, 2021 , Jacobi and Vaidyanathan, 2021 , Yang et al, 2021 , Nguyen et al, 2021 ) and 2 to 3-fold ( Fisher et al, 2020 , Latkin et al, 2021 , Saluja et al, 2021 , Caban-Martinez et al, 2021 ) higher chance of being COVID-19 vaccine hesitant, respectively.…”
Section: Resultsmentioning
confidence: 99%
“… 6 , 7 Frequent concerns for vaccine hesitant PwMS were vaccine safety and efficacy and potential short- and long-term side effects. 6 , 8 In addition, most vaccine hesitant PwMS expressed the desire for additional information. 8 Unfortunately, no safety data pertaining specifically to PwMS have been reported from the various SARS-CoV-2 vaccine trials, and extrapolation of the safety data from the general population to PwMS is unclear, largely due to the uncertain impact of DMTs.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 8 In addition, most vaccine hesitant PwMS expressed the desire for additional information. 8 Unfortunately, no safety data pertaining specifically to PwMS have been reported from the various SARS-CoV-2 vaccine trials, and extrapolation of the safety data from the general population to PwMS is unclear, largely due to the uncertain impact of DMTs. We investigated the relationships between sociodemographic/clinical attributes and DMT status on short-term (24 hours) SARS-CoV-2 vaccine reactogenicity in PwMS participating in an online research network.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations